Ganjiang Bridge: A High-Speed Railway Long-Span Cable-Stayed Bridge Laying Ballastless Tracks. Issue 1 (2nd January 2021) - Sheng, Xingwang; Zheng, Weiqi; Zhu, Zhihui; Yan, Aiguo; Qin, Yongping
Abstract: Ballastless track has been widely used in high-speed railway in China; however, it has not yet been laid on the high-speed railway long-span cable-stayed bridges by now. Ganjiang Bridge is a high-speed railway long-span cable-stayed bridge which is designed to lay ballastless tracks. This bridge type and parts of the local structures are first applied in the high-speed railway bridges. This study highlights the case features and structural characteristics of Ganjiang Bridge. A series of structural measures have been taken to improve the feasibility of laying ballastless tracks on the long-span cable-stayed bridges. Besides, as the critical structure of a long-span cable-stayed bridge, the new type cable-girder anchorage structure in Ganjiang Bridge is safe and reliable. Multi-scale finite element modeling technique can simply and effectively realize the accurate stress analysis of the local structures like the cable-girder anchorage region in long-span cable-stayed bridges. Finally, a brief account of the construction method of this bridge type is introduced.